مؤشرات كفاءة تجارة مصر الخارجية مع الدول الأفريقية العربية: دراسة في الجغرافية الاقتصادية - أحمد، أحمد رجب عبدالرازق (جامعة بني سويف - كلية الآداب, 2023)
ركزت الدراسة على قياس كفاءة تجارة مصر الخارجية مع الدول الأفريقية العربية، وذلك من خلال تطبيق عدة مؤشرات أهمها مؤشر الطاقة الاستيعابية، مؤشر درجة الانكشاف الاقتصادي، متوسط الميل للتصدير، ومتوسط الميل للاستيراد، معامل التركز الجغرافي، معامل التركز السلعي، وذلك للوقوف على مدى استفادة مصر من التجارة مع الدول الأفريقية وخرجت الدراسة بعدد من النتائج والتوصيات، كما تحققت من الفرضيات التي افترضها الباحث. The study focused on measuring the efficiency of Egypt's foreign trade with Arab African countries, through the application of several indicators, the most important of which are the absorptive capacity index, the degree of economic exposure, the average tendency to export, the average tendency to import, the geographical concentration coefficient, the commodity concentration coefficient, in order to determine the extent to which it benefits Egypt from trade with African countries, and the study came out with a number of results and recommendations, and verified the hypotheses hypothesized by the researcher.
Keywords: الجغرافية الاقتصادية -- التجارة الخارجية -- التبادل التجاري -- مصر